Ao encontro dos meninos : a configuração da política social de atendimento a adolescentes em conflito com a lei no estado do Rio de Janeiro a partir do processo de Reforma do Estado (1994-2002) - Moreira, Celeste Anunciata Baptista Dias (2007)
This is a research on the process of statization of the system attending law-offending adolescents in Rio de Janeiro State (Brazil). The primary and most important elements constituting this conversion policy in the State are identified, as well as the form that this policy assumed between the years of 1994 and 2002. For such purpose, this study was designed on the basis of three axes: the Reformation of the State, as a guiding macroeconomical factor of this social policy; service decentralization, as a political landmark supported by the 1988 Federal Constitution and the DEGASE (General Department for Social and Educational Actions), as a materialization of the Public Power proposal for assistance of adolescents, in fulfillment of a socio-educational measure. The employed methodology consisted of there stages: collection and review of the documentation and existing projects on this matter, the statements of eight professionals working at DEGASE within the above-mentioned period and the statements of seven relapsing adolescents, which were interned in the aforementioned system at that time. As regards the first axis, the analysis indicated the way the Reformation of the State interfered with DEGASE organization; as regards the second axis, the analysis was conducted to obtain, from the given testimonies, a description of system formation, as a space for confront of forces, development of social projects and, overall, constitution of the logics for disciplinarization and criminalization of poverty. The third axis focused on the statements given by the assisted adolescents, who pointed out the ambiguities and contradictions of a protective system that many times acts starting from the violation of individual rights. The conducted study aims to contribute to the management of such policy, in order to stimulate the discussion on the currently employed methods to discipline the assisted adolescents and the professionals working in the socioeducational system